Neonatal formulary 7 : drug use in pregnancy and the first year of life - Ainsworth, Sean Brian, 1964- (Chichester, West Sussex ; Ames, Iowa : John Wiley & Sons Inc., 2014)
Neonatal Formulary is a unique publication that provides comprehensive guidance on the safe use of all the drugs prescribed during pregnancy and commonly given to babies during labour, delivery, and the first year of life. This new edition provides improved and detailed coverage of the many drugs that are given to women during pregnancy and during lactation where the baby's welfare must be borne in mind as well as that of the mother. Thus the whole ''pregnancy through to parenthood'' journey is treated as a continuous event with information about drug use and the effects of drugs at all stag.
Renal failureRoyal College of Obstetricians and Gynaecologists; Royal College of Paediatrics and Child Health; UNICEF UK Baby Friendly Initiative; Teratogens; This book; Travel advice; US Food and Drug Administration; World Health Organisation; Part 2 Drug monographs; Part 3 Maternal medication and its effect on the baby; Introduction; Further reading; Reference texts on drug use during pregnancy and lactation; Further information; Maternal medication and the baby; Index: Including synonyms and abbreviations.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Newborn infants -- Effect of drugs on; Obstetrical pharmacology; Pharmacopoeias -- Great Britain; Newborn infants -- Effect of drugs on; Obstetrical pharmacology; Pharmacopoeias -- Great Britain; MEDICAL -- Gynecology & Obstetrics; Newborn infants -- Effect of drugs on; Obstetrical pharmacology; Pharmacopoeias; Great Britain; Electronic books